A novel and efficient synthesis of 3-aryl and 3-heteroaryl substituted-1H-indazoles and their Mannich derivatives - Servi, S; Akgün, ZR (Marcel Dekker Inc, 2002)
A general and highly convenient procedure for the synthesis of 3-heteroaryl and 3-aryl substituted-1H-indazoles has been developed. These compounds (3a-f) were synthesized in good yield by refluxing the NaHSO3 adduct of heteroaromatic and aromatic aldehyde and phenyl hydrazine in DMF. This procedure is more general and shorter than earlier methods. Five new 3-hetero-aryl substituted-1H-indazoles were synthesized and characterized. New Mannich derivatives of 3-(1H-pyrrol-2-yl)-1H-indazole (3a) and 3-(1H-indol-3-yl)1H-indazole (3b) were prepared from morpholine and formaldehyde.